PERLINDUNGAN EKSPRESI BUDAYA TRADISIONAL MASYARAKAT ADAT MELAYU DI PROVINSI RIAU - Tengku Mega Rahmadini; Zulfikar Jaya Kusuma; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Traditional cultural expressions are knowledge, skills and practices that are developed, maintained and passed down from generation to generation in society, which often forms part of the cultural or spiritual identity of that society. At present there is no clear protection and regulation of the potential that comes from traditional knowledge and traditional cultural expressions from both economic and moral aspects so that they can be claimed by foreign parties or commercialized without sharing the benefits to the bearer community. The purpose of this study is to determine the protection of traditional cultural expressions of Malay indigenous peoples in Riau Province, to find out legal and non-legal issues that are obstacles in protecting traditional cultural expressions of Malay indigenous peoples in Riau Province, and to find a way out of the problem of protecting cultural expression traditional Malay traditional community in Riau Province. The type of research or problem approach that will be used in this research is normative juridical, namely research conducted by examining secondary legal material or research based on standard rules that have been recorded is also called library research.Protection of folklore in the Copyright Act has not been effective, the protection is still difficult to implement, because until now the Government Regulation referred to in article 38 paragraph (4) of Law number 28 of 2014, does not yet exist. Legal constraints in protecting the traditional cultural expressions of Riau Province include: regulation of related rights that are ignored, there are no implementing regulations due to the absence of Government Regulation referred to in Law Number 28 of 2014, and the delays in the formation of the Draft Law on Traditional Knowledge and Expression Traditional cultures that have not yet been ratified, non-legal constraints include: indigenous communities that are communalistic and put forward the concept of community, the concept of folklore as intellectual property has not yet been fully accepted by indigenous peoples, and indigenous peoples who do not care about protection efforts. To get world recognition for national cultural heritage, Indonesia must follow the stages and format determined by UNESCO.Keywords: Protection of Folklore, Traditional Cultural Expressions, Indigenous Peoples.